Pelaksanaan Program Pemerintah Bantuan Pangan Non Tunai (BPNT) dalam Rangka Mitigasi Dampak Covid – 19 di Kelurahan Sokanegara - Veti Fadillah; Pangestika Rizki Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The Covid-19 pandemic is a viral pandemic originating from China that entered and began to spread to Indonesia in 2019, this virus has long spread and has claimed many victims as many as 1,566 died in the latest data on August 23, 2021. The role of the government in handling cases Covid-19 is said to be good, with the rules for the use of masks, PSBB, PPKM, vaccinations etc., it is quite helpful and prevents the transmission of this virus. In the economic field, the government is also sufficient to provide great assistance to the impact of this pandemic, as for the assistance provided there is PKH (Programme Family Hope), BPNT (Non-Cash Food Assistance), BST (Cash Social Assistance) and then there is a program from the Banyumas district government, namely JPS (Social Safety Net), since the covid-19 pandemic, many people have been affected, especially in Sokanegara village, Purwokerto. East, where most of the people make a living as traders, entrepreneurs, and labourers, many are experience bankruptcy in their daily lives, the imbalance between increasing economic needs and drastically reduced income, in this case the government is trying to provide social assistance by increasing the quota for aid recipients, and the initiative from the local Rt and Rw to provide sharing programs to those who do not receive and experiencing the impact of the Covid-19 pandemic. This research method was carried out to examine how residents did welfare for their neighbors who were affected and who did not receive this assistance, the method used was a qualitative method by conducting family interviews.